Rethinking the sexual contract: The case of Thomas Hobbes. (March 2020) - Rustighi, Lorenzo
Feminist scholars have long debated on a key contradiction in the political theory of Thomas Hobbes: While he sees women as free and equal to men in the state of nature, he postulates their subjection to male rule in the civil state without any apparent explanation. Focusing on Hobbes's construction of the mother–child relationship, this article suggests that the subjugation of the mother to the father epitomizes the neutralization of the ancient principle of 'governance', which he replaces with a novel concept of 'power' as formally authorized command. This scrutiny leads to three main conclusions: (1) a radicalization of Pateman's concept of 'sexual contract'; (2) the acknowledgement that patriarchy is inseparable from the logic of political authority constructed by Hobbes; and (3) the claim that criticism of patriarchal rule requires an overall problematization of the mainstream conception of political participation we have inherited from modern political science.